HUBUNGAN KONSEP DIRI DENGAN PEMECAHAN MASALAH PADA REMAJA DI DESA GEDANGAN KECAMATAN GROGOL SUKOHARJO - Ariasti, Dinar; Wartanti, Nivela Aprilia (Jurnal Kesehatan Holistic, 2017)
The subjects: the population in this study were all teenagers in the village Gedangan, based on an initial survey found as many as 44 teenagers. Methods This study is an analytic correlation with cross sectional approach. Data collection tool used is a questionnaire to measure self-concept and problem solving by finding primary data fRPS Gedangan. The results of the study there were 36 respondents used the concept of self-adaptive and 8 respondents use maladaptive self-concept, 36 respondents made good problem solving and 8 respondents perform troubleshooting poorly. The results of Chi-Square test with SPSS version 18.0 with ? = 5% (0.05), p = 0.000 thus obtained p value of <0.05, which means that Ho refused and Ha accepted. The conclusion of this study there is a relationship between self concept with problem solving in teenagers in the Gedangan village Grogol Sukoharjo